Magnetometric exploration in intrusive basic with evidence of gold in northern region of the Camaquã Sedimentary Basin (RS) - Pereira, Alice Marques [UNESP]; Moreira, César Augusto [UNESP]; Bortolin, José Ricardo Melgues; Lopes, Syngra Machado [UNESP]; Nardy, Antonio José Ranalli [UNESP] (FapUNIFESP (SciELO), 2015)
This study involved magnetometric exploration in the region of São Sepé (RS), southern Brazil, to evaluate the potential for gold mineralization in a gabbro using evidence previously obtained from the geochemical exploration of stream sediments. The gabbro named Santa Catarina is intruded in the Metamorphic Complex Vacacaí, a metassedimentary sequence where several gold deposits were recognized. In this study, nine lines of land magnetometry were performed with 1.200m in length each, a total of 10.800m and 720 reading stations. The results suggest the presence of filonian mineralization in fractures, some of which are subject to weathering action, releasing and transporting gold by water action and depositing it along the stream sediments downstream from the gabbro. The analytical signal map outlines areas of high magnetic susceptibility within its boundaries, coinciding with structural lineaments in the NS and EW directions, associated with the last of the four stages of regional deformation, possibly responsible for both fracturing and opening of spaces in the gabbro, as by remobilization of sulfide and gold recognizably described in several gold deposits within the Vacacaí Metamorphic Complex.

Esse estudo consiste na aquisição de dados magnetométricos na região de São Sepé (RS), sul do Brasil, com o propósito de avaliar o potencial de mineralização aurífera de um gabro, a partir de indícios obtidos em prospecção geoquímica de sedimentos de corrente prévios. O gabro denominado Santa Catarina está intrudido no Complexo Metamórfico Vacacaí, uma sequência metassedimentar ,onde foram reconhecidas diversas jazidas de ouro. Nesse estudo, foram realizadas nove linhas de magnetometria terrestre, com 1.200 m de comprimento cada, num total de 10.800 m e 720 estações de leitura. Os resultados sugerem a presença de mineralizações filonianas em fraturas, algumas das quais sujeitas à ação intempérica, com liberação e transporte de ouro por ação fluvial e deposição junto a sedimentos de corrente a jusante do gabro. O mapa de sinal analítico descreve as áreas de alta susceptibilidade magnética dentro de seus limites, coincidentes com lineamentos estruturais nas direções NE e E-W, associadas a à última das quatro fases de deformação regional, possivelmente responsável, tanto por fraturamento e abertura de espaços no gabro, quanto pela remobilização de sulfeto e ouro reconhecidamente descritos em diversas jazidas de ouro no âmbito do Complexo Metamórfico Vacacaí.
Keywords: Mineral exploration; Gabbro; Fracture; Analytic signal; Exploração mineral; Gabro; Fratura; Sinal analítico